IMPLEMENTASI METODE USMANI DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN DI TK AL-FITYAN SCHOOL TANGERANG - Miftahul Fakhrah; Hulailah Istiqlaliyah (Fakultas Tarbiyah IIQ Jakarta, 2023)
The research purpose was to describe the ability to read the Qur'an in Al-Fityan School Tangerang Kindergarten while applying the Usmani Method of learning the Qur'an. This research uses descriptive qualitative research. Methods of data collection were solved using observation, interviews, and documentation. The data analysis techniques are data reduction, data presentation, and concluding. The results showed that the implementation of the Usmani method in improving the ability to read the Qur'an at Al Fityan School Tangerang Kindergarten was running effectively as evidenced by the achievement of graduate targets, and the results of routine evaluations held, and the achievements of students at Al Fityan School Tangerang Kindergarten.